Strategic renewal and its impact on enhancing the strength of expertise: A survey study of a sample of private banks – Baghdad - Al-Mulla, Hamid Ali Ahmed; Khalif, Nisreen H (Edelweiss Applied Science and Technology, 2024)
The study aims to form comprehensive intellectual visions and clear perceptions about the relationship between strategic renewal and the strength of expertise in light of the major changes in the business environment and the knowledge-based economy, in an attempt to generalize the model and the extent of its applicability in the Iraqi environment. The study was launched from an intellectual problem represented by the existing intellectual disparity due to the novelty of the subject and to bridge the knowledge gap between philosophical proposals and application, with the aim of identifying the impact of strategic renewal in enhancing the strength of expertise. The study relied on the descriptive analytical approach by deriving hypotheses and testing them based on a questionnaire distributed to (124) senior management, employees, and managers of departments and divisions in a sample of private commercial banks in Baghdad. To analyze the data, statistical methods and tools were used to analyze the data through statistical programs (SPSS), (AMOS 23). The results showed the validity of all the main and sub-hypotheses of the study. Based on that, a set of conclusions were formulated that recommend the necessity for private commercial banks to increase investment in strategic renewal and focus on renewing ideas and developing banking services provided to customers and keeping pace with developments in banking services provided in developed countries.